Visual Determination of Transformer Oil Quality Parameters - Kozlov V.K.; Valiullina D.M.; Kurakina O.E. (Problems of the Regional Energetics, 2021)
During operation of the transformer, the oil in it undergoes profound changes usually referred to as aging. The electrical insulating properties of it deteriorate, and sediments accumulate on the active part, which makes it difficult to remove heat. Inhomogeneous solid formations can induce not only the voltage breakdown, but also impair the parameters such as viscosity and other char-acteristics of the oil, which are important for the reliable operation of the power transformers. Aromatic groups initially is present in the transformer oil composition during the operation of the oil, and because of the aging processes, the concentration of the unsaturated cyclic com-pounds increases. The aim of this work is to develop a new method for the determination of the aromatic compounds and colloidal particles. This goal is achieved using a visual inspection of the transformer oil samples in the visible range. The most significant result of the paper is the establishment of a correlation between the acid number of the transformer oil (KOH), the tan-gent of the dielectric loss angle and the type of oil image under the visible light illumination. The significance of the obtained results lies in the fact that the presented method based on the analy-sis of the scattered and transmitted radiation, makes it possible to determine the presence of the aromatic compounds and colloidal particles in the transformer oil, as well as to define their con-centration and size. This method simplifies the analysis of the transformer oil quality, and re-duces the cost of the research, which is an important factor for the electric power industry.